New insight for metformin against bladder cancer - EL-Arabey, Amr Ahmed (Genes Environ, 2017)
International Agency for Research on Cancer (IARC) estimated that bladder cancer is the ninth most common cancer in the world, with 430,000 new cases and 165,000 deaths in 2012. Bladder cancer represents the fourth most common cancer in men and ninth most common cancer in women. It is the second most prevalent cancer in men 60 years of age or older in United States. Looking further down, continuing advancements in cancer research could potentially offer more choices for clinician and patient with longer survival and better quality of life. Although, bladder cancer represents an ideal tumor model to test and apply cancer prevention strategies; there are limited studies about application of metformin in the management of bladder cancer. Here, I will shed light on the proposed mechanisms of anti-carcinogenic effects of metformin and cohort of these mechanisms with the novel application of metformin as therapy of bladder cancer.